Enterocyte Culture on a Hybrid Transwell-Inserted Gut-on-a-Chip for Liquid–Liquid and Air–Liquid Interface Conditions - Tidaporn Charoensri; Kornphimol Kulthong; Pareesa Pormrungruang; Ratjika Wongwanakul; Chanikarn Kunyanee; Sasitorn Aueviriyavit; Sakon Rahong (ACS Omega, 2025)
fluid flow system for culturing Caco-2 cells.
Keywords: 3D Printing in Biomedical Research; Microfluidic and Capillary Electrophoresis Applications; Innovative Microfluidic and Catalytic Techniques Innovation